Evaluation of the Independent Curriculum P5RA Program at Madrasah Ibtidaiyah Unggulan Al Fadel, Tajurhalang-Bogor - Farah, Farah; Zulaikha, Siti; Listyasari, Winda Dewi (Electronic Journal of Education, Social Economics and Technology, 2025)
This study aims to evaluate the effectiveness of the implementation of the Pancasila and Rahmatan lil 'Alamin Student Profile Strengthening Program (P5RA) at Madrasah Ibtidaiyah Unggulan Al Fadel Bogor. The P5RA program, which has been running since the 2022/2023 school year as part of the Independent Curriculum, is designed to strengthen the values of Pancasila and the principles of Rahmatan lil 'Alamin in students. This study uses the CIPP (Context, Input, Process, Product) evaluation model to analyze four main aspects: the context of implementation, the availability of resources, the implementation process, and the results and impact of the program. The research method is qualitative with a descriptive approach, involving teachers, educators, and students as research subjects. Data were collected through observation, semi-structured interviews, and documentation studies, then analyzed using the Miles and Huberman model. The results showed that P5RA succeeded in increasing students' involvement in project-based learning and strengthening their character, such as independence, tolerance, and responsibility. A contextual evaluation revealed that the program not only met policy demands but also answered students' needs for holistic character education. From the input aspect, the availability of human resources and supporting facilities is the key to the success of the program. However, the study also identified challenges such as time constraints, lack of standardization of evaluations, and lack of socialization to parents. Overall, P5RA has proven to be effective in shaping student character, although improvements are needed in the evaluation and management aspects to ensure the sustainability of the program.